An Argument for Documenting Casualties Violence Against Iraqi Civilians 2006 - Hall, Katharine (RAND Corporation, 2008)
This study examines available open-source data on Iraqi civilian fatalities and assesses problems associated with previous collection efforts. The authors present a new and more robust RAND Corporation Iraqi civilian violence dataset from which they derive observations about trends in targeting and weapons in 2006. These findings lead to a proposed framework for future civilian fatality data-collection efforts in Iraq and beyond.